Anatolij Kuznecov, Babij Jar. Romanzo-documento (Milano, Adelphi, 2019, 454 pp. ISBN 978-88-459-3347-9) (Altre Modernità, 2020)
Anatolij Kuznecov, Babij Jar. Romanzo-documento (Milano, Adelphi, 2019, 454 pp. ISBN 978-88-459-3347-9)di Valentina Marcati